Efektifitas Prenatal Yoga Menggunakan Tehnik Hypnobirthing dalam Menurunkan Kecemasan pada Ibu Primigravida Trimester II dan Trimester III Dalam Menghadapi Persalinan di Puskesmas Simarimbun Kota Pematangsiantar - Bangun, Parmiana; Sembiring, Ribka Nova (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Anxiety and worry in pregnant women if not handled seriously will have an impact and influence on the physical and psychological aspects of both the mother and the fetus. Apart from that, there is a natural alternative that pregnant women can do to make their souls calmer with positive energies and help relieve pain during contractions and can speed up the labor process, namely the hypnobirthing relaxation technique. According to Nascimento, mothers with normal pregnancies should be supported to carry out moderate intensity physical exercise to obtain benefits during pregnancy and the birth process. One way to improve maternal health during pregnancy until the postpartum period is to carry out supporting activities, namely yoga during pregnancy. Yoga is a sport that is fun and good for body health. Objectives: To analyze the effect of prenatal yoga using hypnobirthing on reducing anxiety in primigravida mothers, to analyze the effect of prenatal yoga using hypnobirthing on respiratory changes in primigravida mothers, to analyze the effect of prenatal yoga using hypnobirthing on changes in blood pressure in primigravida mothers, to analyze the effect of prenatal yoga Using Hypnobirthing for Weight Gain in Primigravida Mothers. Benefits Can increase knowledge in the field of midwifery care, especially in midwifery practice, especially midwifery care during pregnancy, namely in the practice of Prenatal Yoga exercises. The research method in this research is that this research uses a Quasi Experimental design with a Pretest-Posttest Group Design approach. A pretest was carried out in the intervention group and control group regarding reducing anxiety, blood pressure, respiration and maternal weight before implementation. The research sample was selected using a random permuted blocks technique with a sample size of 20 respondents. Data analysis in the study was the difference between anxiety scores and blood pressure and respiration in the intervention and control groups, which were analyzed using the Mann Whitney test. Analysis of the effect of Prenatal Yoga using Hypnobirthing on anxiety levels and changes in blood pressure and breathing in both groups using the Chi Square test. The significance of test results is determined based on a p value <0.05. They still have skills that can be applied to society, especially pregnant women. Keywords: Anemia, Pregnant Women, Booklet  ABSTRAK Kecemasan dan kekhawatiran pada ibu hamil apabila tidak ditangani dengan serius akan membawa dampak dan pengaruh terhadap fisik dan psikis baik ibu maupun janinnya. Selain itu, terdapat satu alternatif alami yang bisa dilakukan oleh ibu hamil untuk membuat jiwa menjadi lebih tenang dengan energi-energi positif dan membantu meringankan rasa sakit saat kontrksi serta dapat mempercepat proses persalinan adalah dengan teknik relaksasi hypnobirthing. Untuk Menganalisis Pengaruh Prenatal Yoga menggunakan Hypnobirthing terhadap Penurunan Kecemasan pada Ibu Primigravida, Untuk Menganalisis Pengaruh Prenatal Yoga menggunakan Hypnobirthing terhadap Perubahan Pernafasan pada Ibu Primigravida, Untuk Menganalisis Pengaruh Prenatal Yoga menggunakan Hypnobirthing terhadap Perubahan Tekanan darah pada Ibu Primigravida, Untuk Menganalisis Pengaruh Prenatal Yoga menggunakan Hypnobirthing terhadap Penambahan Berat Badan pada Ibu Primigravida. Manfaat Dapat meningkatkan keilmuan di bidang asuhan kebidanan terutama dalam praktik kebidanan, khususnya asuhan kebidanan pada kehamilan yaitu pada praktik senam Prenatal Yoga. Metode Penelitian dalam penelitian ini adalah penelitian ini menggunakan rancangan Quasi Exprimental dengan pendekatan Pretest-Posttest Grup Design. Pretest dilakukan pada kelompok intervensi dan kelompok kontrol mengenai Penurunan Kecemasan, Tekanan Darah, Pernafasan dan Berat Badan Ibu sebelum pelaksanaan. Sampel penelitian dipilih dengan menggunakan teknik random permuted blocks dengan besaran sampel 20 Responden. Analisis data dalam penelitian adalah perbedaan antara skor kecemasan dan tekanan darah, pernafasan pada kelompok intervensi dan kontrol dilakukan analisis dengan menggunakan uji Mann Whitney. Analisis pengaruh Prenatal Yoga dengan menggunakan Hypnobirthing terhadap tingkat kecemasan dan perubahan tekanan darah, pernafasan  pada kedua kelompok menggunakan uji Chi Square. Kemaknaan hasil uji ditentukan berdasarkan nilai p<0,05mereka tetap mempunyai keterampilan yang dapat dapat diaplikasikan kepada masyarkat terutama pada ibu hamil. Kata Kunci: Anemia, Ibu Hamil, Booklet